The Impact of E-Integrated Marketing Communication (E-IMC) on Brand Equity for New College - Fardiansyah - Fardiansyah; Salya Rater; D.S Putra (LPPM Politeknik Aceh Selatan, 2021)
This research discusses the impact of the application of E-Integrated Marketing Communication (E-IMC) applied to new universities. This qualitative research refers to the theoretical reference written by John W. Creswell. The sample was determined using the snowball sampling technique and the data collection technique was carried out by in-depth interviews (in-depth interview) and documentation. This study aims to describe the impact of the application of integrated marketing communications applied by polytechnic universities. The findings indicate that user experience affects the E-IMC typology used. E-IMC affects brand equity in higher education. Further research can avail a research model and test the model with quantitative studies with the addition of demographic factors. Because the object of this research is a new polytechnic type of university, the different types of tertiary institutions can also be an additional variable to be studied further.